Letramento literário na sala de aula: as práticas pedagógicas de leitura e a atuação do aluno leitor - Brasileiro, Aparecida de Fátima (Universidade Federal de São Carlos, 2020)
This research brings the result of the investigation of Pedagogical Practices of Literary Reading and the performance of the student/reader in a state public school of Guanambi (BA). As a theoretical framework, the research used the concepts of literacy centered on Street and Soares from an ideological perspective; Barton & Hamilton, using the notions of literacy practices and literacy events, especially the reflections of literary literacy studies of Cosson and Paulino; literature teaching reflected by Zilberman, Todorov, Marisa Lajolo; literary reader discussed by Lena Lois, Piglia and Michèle Petit. As a complementary support, this research was guided by the concepts of Marcia Abreu, Neide Rezende, Dalvi, among others. The problem led this thesis to the following question: how are the pedagogical practices of literary reading mediated and how is the performance of high school students/readers during the development of methodological practices of literary reading? To look for an answer for this investigation, it was defined as a qualitative research, based on ethnography as a methodological basis, to verify how the daily life of the classroom was configured, both in the teaching activities of the subject Portuguese and Brazilian Literature in the 1st, 2nd and 3rd grades of high school, and in the reader's positioning when facing these practices. The corpus of the study comprised data collection through the analysis and interpretation of course syllabus, class observation, interview with three teachers and questionnaire with thirteen students, and the data were described, analyzed and interpreted. The data contributed to the reflection about the teaching mediation and the reader performance in the literary pedagogical spheres, in their varied supports and educational propositions. It was found that there is a diversity of Pedagogical Practices of Literary Reading, not consisting of rules to be followed, but of constructions in accord with the reality of the teaching context. This multiplicity demonstrated a dialogical relationship among the teaching community and encouraged the reader's performance. This performance was frequent, even non-literary readers made use of Reading Simulation Strategies to demonstrate their performance. As a result, it was verified the need to take the data to be reflected with the educators, in order to encourage the research about the reader and to promote mediation practices that allow the discursive exchange and the reflection about the teaching-learning process.
Literary literacy in the classroom: pedagogical practices of reading and the acting of the student reader
Keywords: Prática pedagógica de leitura literária; Mediação docente; Atuação do leitor; Eventos de letramento; Letramento literário; Pedagogical Practice of Literary Reading; Teaching Mediation; Reader Performance; Literacy Events; Literary Literacy; LINGUISTICA, LETRAS E ARTES::ARTES